Inhibition of junctional protein disruption by 2,4,6-trihydroxy-3-geranyl acetophenone in lipopolysaccharide-induced endothelial hyperpermeability via GEF-H1/RhoA/ROCK pathway - Chan, Yee Han; Liew, Kong Yen; Rullah, Kamal; Harith, Hanis Hazeera; Tan, Ji Wei; Israf, Daud Ahmad; Shaari, Khozirah; Marcus, Mexmollen; Tham, Chau Ling (Springer Science and Business Media Deutschland GmbH, 2025)
2,4,6-Trihydroxy-3-geranyl acetophenone (tHGA) is a bioactive phloroglucinol compound found in the leaves of Melicope pteleifolia (Champ. ex Benth.) T.G.Hartley. Our previous study has proven that tHGA exhibited significant in vitro barrier protective effects against lipopolysaccharide (LPS) induction, mainly by inhibiting endothelial hyperpermeability via attenuation of F-actin cytoskeletal rearrangement, as F-actin cytoskeleton is anchored to junctional proteins such as zonula occluden (ZO)-1, occludin, and vascular endothelial-cadherin (VE-cadherin), and they play collaborative roles in the preservation of endothelial integrity. Therefore, the effects of tHGA on these junctional proteins were further investigated, followed by the dissection of signalling pathways mediated by tHGA in suppressing LPS-induced junctional protein disruption during endothelial hyperpermeability. HUVECs were pretreated with tHGA prior to LPS induction. TEER, immunofluorescence staining, Western Blotting, and RT-qPCR were performed to examine the effects of tHGA on junctional proteins in terms of their integrity, localization, protein expression, and gene expression, respectively. Proinflammatory signalling molecules including MLC, NF-κB p65, p38 MAPK, ERK MAPK, and JNK MAPK were assessed to unravel the underlying signalling pathways, followed by molecular docking on human ROCK1 to predict the molecular target of tHGA. tHGA profoundly preserved junctional integrity by inhibiting both delocalization and downregulation of ZO-1, occludin, and VE-cadherin, via inactivation of MLC, NF-κB p65, p38 MAPK, and ERK MAPK, which are mainly diverged from GEF-H1/RhoA/ROCK pathway. ROCK1 was predicted as the molecular target of tHGA. tHGA should be developed as a potential therapeutic remedy for prevention and/or treatment of permeability-related disorders.